Micrometry of Testis in Gaddi Sheep Foetii - Shukla, Parul (Indian Journal of Veterinary Anatomy, 2019)
The present study was conducted on sixty eight male Gaddi sheep foetii ranging from 36th day to 140th day of gestation and were divided into four stages on the basis of their age. The micrometrical parameters like capsular thickness, tubular diameter, diameter of cells-peritubular cells, large and small cells, Sertoli cells andleydig cells and diameter of their nuclei gradual increase with the progression of gestation. However, there was no significant difference among different micrometrical parameters with respect to right and left testis.